2006
DOI: 10.1111/j.1365-3016.2006.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse perinatal conditions in hearing‐impaired children in a developing country

Abstract: Prevailing adverse perinatal conditions in developing countries have been associated with substantial mortality, but little evidence exists on their impact on permanent childhood disabilities and morbidity due to limitations in clinical investigations and medical records. This study aims to identify the possible association between parent-reported adverse perinatal conditions and permanent hearing loss, in order to establish service needs within current maternal and child health programmes. Structured question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
1
28
1
Order By: Relevance
“…Two separate Nigerian studies indicated a prevalence of 4.9% in a sample of children diagnosed with SNHL [45] and 13.5% in a cohort of children with severe-profound hearing loss [44]. Hyperbilirubinemia has been associated as the most commonly reported risk factor for ANSD, varying between 30 to 70% [38,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Two separate Nigerian studies indicated a prevalence of 4.9% in a sample of children diagnosed with SNHL [45] and 13.5% in a cohort of children with severe-profound hearing loss [44]. Hyperbilirubinemia has been associated as the most commonly reported risk factor for ANSD, varying between 30 to 70% [38,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…24 Delayed neonatal adaptation ('birth asphyxia') was indexed by parental report of 'delayed cry' of the baby at birth for more than 2 minutes or the application of prolonged physical stimulation to bring about respiration in the newborn baby. 25,26 Parental reporting of jaundice in the first week of life requiring hospital admission for phototherapy or exchange blood transfusion was considered reliable being an episodic event. 25 Eliciting neonatal jaundice not necessitating hospital referral or admission was also considered reliable in dark skin babies because of its high prevalence and the familiar discolouration of the sclera and mucous membranes as well as the traditional therapies commonly associated with this condition in this population.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Parental reporting of jaundice in the first week of life requiring hospital admission for phototherapy or exchange blood transfusion was considered reliable being an episodic event. 25 Eliciting neonatal jaundice not necessitating hospital referral or admission was also considered reliable in dark skin babies because of its high prevalence and the familiar discolouration of the sclera and mucous membranes as well as the traditional therapies commonly associated with this condition in this population. Neonatal jaundice in this study is abbreviated as NNJ and used interchangeably with hyperbilirubinaemia.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the etiology of hearing loss, more than 50% of cases are due to hereditary factors, with at least 120 genetic loci involved in nonsyndromic hearing loss (NSHL) and greater than 60 known for autosomal recessive NSHL ( Smith et al, 2005;Samanich et al, 2007). The rest of the cases are attributable to prenatal, perinatal, and postnatal life conditions (Lasisi et al, 2006;Olusanya & Okolo, 2006;Olusanya & Solanke, 2009).…”
mentioning
confidence: 98%